2017
DOI: 10.1371/journal.pone.0170055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adding a Decision Aid to Patient Education in Adults with Asthma: A Randomized Clinical Trial

Abstract: BackgroundNot providing adequate patient education interventions to asthma patients remains a major care gap. To help asthma patients and caregivers discuss inhaled controller medication use, our team has previously developed a decision aid (DA). We sought to assess whether adding this DA to education interventions improved knowledge, decisional conflict, and asthma control among adults with asthma.MethodsA parallel clinical trial (NCT02516449). We recruited adults with asthma, aged 18 to 65 years, prescribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 66 publications
0
33
0
1
Order By: Relevance
“…Patients in this study were satisfied with the patient-centred counselling, as has been shown in earlier research (Rajala et al 2018). More specifically, previous studies have proposed that patient-centred counselling supports patient decisionmaking (Gagne et al 2017) and promotes the selfmanagement of asthma (Rajala et al 2018). In this study, patients who had been subjected to an asthma test were more likely to be satisfied with counselling.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Patients in this study were satisfied with the patient-centred counselling, as has been shown in earlier research (Rajala et al 2018). More specifically, previous studies have proposed that patient-centred counselling supports patient decisionmaking (Gagne et al 2017) and promotes the selfmanagement of asthma (Rajala et al 2018). In this study, patients who had been subjected to an asthma test were more likely to be satisfied with counselling.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, subjecting a patient to an asthma test was found to significantly influence satisfaction with counselling among the respondents of this study and, as such, should be studied further both in Finland and international contexts. This type of research is important from patient and societal perspectives, as high-quality counselling has been shown to reduce hospital admissions (Gagne et al 2017) and improve lung function (Gibson et al 2009) among asthma patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional file 3 presents the risk of bias assessment on the outcome level per study. Besides the study of Gagné et al [ 29 ], all studies have an unclear or high risk of bias for all outcomes assessed in this review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%